CAPABILITY MODEL AND COMPETENCE MEASURING FOR SMART HOSPITAL SYSTEM: AN ANALYSIS FOR TURKEY - Banu ÇALIŞ USLU (Rojan GÜMÜŞ, 2020)
Today, rapidly developing technological innovations affect and change all sectors. Health sectors are inevitably involved in a digital transformation. In this transformation, IoT technology plays an important role, which enables many devices to connect and work together. IoT basically converts systems into intelligent systems that work together using sensors, connection methods, internet protocols, databases, cloud computing and analytics as infrastructure. In this respect, it is necessary to establish the necessary technical infrastructure and establish a suitable environment for the establishment of intelligent hospitals. Finally, a capability model has been developed in order to measure digital performance of Turkey. For Turkey health sector, technology assessment report is presented based on survey results and HIMMS EMRAM data.